A Study of Physiological Structure and Element Composition of Fibers at Burial with Different pH Values - Ruangkasa, Sirirat; Vichuwanich, Woratouch (Journal of Applied Research on Science and Technology (JARST), 2021)
The objectives of this study were to (1) comparatively examine the physiological structure and (2) identify the element composition of both natural and synthetic fibers that had been periodically landfilled with acid and alkaline soil. Three fiber materials including cotton, silk and polyester were buried in the known pH soil at different session of time and subsequently analyzed by the Scanning Electron Microscope/Energy Dispersive X-ray Spectroscopy (SEM/EDX). At a 30-day session: all cotton fibers revealed a shrunk and oval shape in the acid soil, while its major element composition (Carbon (C) and Oxygen (O)) were relatively equal in amount; 64.81% of C and 33.73% of O in an acidic condition and 64.82% of C and 33.73% of O in the alkalinity. Cotton fibers in the alkaline soil showed a triangle shape with more areas of torn surfaces than those in the acidity, and were comprised of 4 major elements namely C (42.21%), O (41.81%), Silicon (Si) (2.39%), and Calcium (Ca) (12.61%), while its composition in the acidic soil were C (61.57%), O (34.75%), Silicon (Si) (1.46%), and Calcium (Ca) (1.51%). Polyester fibers under the acidic landfill revealed a characteristic of rough surface with a flattened and round edge and held more amounts of soil particles than those of the alkalinity. Interestingly, apart from its element composition base (C and O), Si was found under the acidic condition whereas Ca was prominent in the alkalinity. At the 15-day session, a minor change was observed. The resultant findings indicated that physiological structure and element composition of fibers could be identified and be a useful tool in the forensic facets while the technique used was neither destructive nor time consuming.